Is pupil attainment higher in well-managed schools?. Issue 1 (2nd January 2023) - Bryson, Alex; Stokes, Lucy; Wilkinson, David
ABSTRACT: Linking the Workplace Employment Relations Surveys 2004 and 2011 to administrative data on pupil attainment in England we examine whether secondary and primary schools who deploy more intensive human resource management (HRM) practices have higher pupil attainment. We find intensive use of HRM practices is positively and significantly correlated with higher labour productivity and quality of provision, and with better financial performance, most notably in primary schools, but it is not associated with higher pupil attainment as indicated by assessment scores at Key Stage 2, Key Stage 4 and value-added measures based on assessments at these points.